Development of bio-inspired electromechanical devices based on PBMA-b-(PSS-r-PS) amphiphilic block copolymer - Saccardo, Matheus Colovati (Universidade Federal de São Carlos, 2024)
Technological advances in the aerospace, biomedical, and robotics industries stimulate the need for innovative and sustainable devices, such as electromechanical devices (EMDs), which are bio-inspired materials capable of mimicking biological systems in appearance, functionality, and operation. For practical applications, EMDs must combine several properties, such as i) high ionic conductivity, ii) flexibility, iii) mechanical resistance, and iv) chemical, thermal, and structural stability. Such properties can be obtained by engineering amphiphilic copolymers, which can self-assemble into well-defined morphologies with nanometric domains. Thus, it is possible to effectively dissociate ionic conductivity from mechanical properties, adjusting the flexibility, Young's modulus, and ionic conductivity according to the size of the blocks and the number of functional groups. Therefore, in this project, reversible addition-fragmentation chain transfer (RAFT) polymerization was used to synthesize the diblock copolymer Poly(butyl methacrylate)-b-(sulfonated polyneopentyl styrene-r-polystyrene) (PBMA-b-( PNeoSS-r-PS)). Subsequent thermolysis of the PNeoSS segments removes the neopentyl group, resulting in a sulfonated polystyrene-r-polystyrene (PSS-r-PS) backbone, yielding an amphiphilic block copolymer with ionic conductivity, which was used to prepare an EMD. In general, it can be concluded that RAFT polymerization is a robust and versatile technique that allows control of the degree of polymerization, molecular weight, polydispersity, and chemical composition of the copolymer. The copolymer presented a molecular weight of 65 kg.mol-1, with a 50% ratio between flexible and rigid blocks, alongside an 8.8% degree of sulfonation, lamellar morphology, capable for enhancing flexibility and ionic conductivity. Finally, the device was tested and characterized electromechanically using an electromechanical characterization system, showing promise for application as a sensor.
Desenvolvimento de dispositivos eletromecânicos bioinspirados baseados em copolímero em bloco anfifílico do tipo PBMA-b-(PSS-r-PS)
Keywords: Electromechanical devices; Amphiphilic block copolymer; Electromechanical response; RAFT polymerization; Sensor; Dispositivos eletromecânicos; Copolímero em bloco anfifílico; Resposta eletromecânica; Polimerização RAFT; Sensor; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS